Information Technology Infrastructure and its Impact on the Innovation Performance of Employees: A Survey Study of the Opinions of a Sample of Employees in Iraqi University Libraries (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The research aims to answer the research question (How can information technology infrastructure affect employee innovation performance?). The dimensions (computers and accessories, software and databases, information and communications networks, and human resources) were adopted to measure the variable of information technology infrastructure. The variable of employee innovation performance was calculated based on the dimensions (flexibility, fluency, originality, and sensitivity to problems). A questionnaire was used as a data collection tool. A research sample of 87 individuals from the study community from the libraries of the University of Karbala was selected using a comprehensive enumeration method, representing 93% of the employees. The community as a whole was studied, and to analyze the sample's responses, a set of statistical methods was adopted, including (standard deviation, response intensity, impact factor, and structural equation modeling). The research came up with some conclusions, including that libraries face limited capabilities in the communications and networking system, which is a decisive factor that negatively impacts the investment in technology to obtain the required support on time or to achieve smooth communication with beneficiaries. The researched libraries are also weak in providing their employees with a specialized technical team for technical support and advice, especially since most are not specialized in office or technology.